Development of walkable photovoltaic floor tiles used for pavement. (1st March 2019) - Ma, Tao; Yang, Hongxing; Gu, Wenbo; Li, Zhenpeng; Yan, Siyun
Highlights: Feasibility study of applying solar photovoltaic floor tile for pavements. Development and experimental test of walkable PV floor tile prototype. Mathematical model development of PV floor for simulation study. Electrical, thermal and mechanical performance evaluation of PV floor. Abstract: Solar road panel is a technology that has the ability to revolutionize the way that roads are built and how electricity is generated. In the current study, the walkable solar PV floor tile is proposed for installation on pavements and cycling tracks for a Green Deck in Hong Kong. Specifically, two solar PV floor tile prototypes are fabricated, and its electrical and thermal performance are tested in the lab and under real conditions. The mathematical model of the developed solar PV floor is also developed, and the simulated result is compared with outdoor tests. Results show that the developed PV floor can achieve satisfactory performance in solar energy conversion, anti-slip performance, heat-resistance and compressive strength, demonstrating that such PV floor tiles can be used as a replacement of the pavements. The developed PV floor can generate power and reduce the material utilization, providing an innovative and green solution to integrate sustainable energy technologies into the park and to achieve the target of zero greenhouse gas emission.